Concordance and reproducibility in the location of reference points for a volumetric craniofacial analysis: Cross-sectional study - Natali Romero-Tapiero; Andrés Giraldo-Mejía; Adriana Herrera-Rubio; Juan Fernando Aristizábal-Pérez (Tabriz University of Medical Sciences, 2023)
Background. Considering the limitations of visualization that occur even with the use of radiographs, the cone beam computed tomography (CBCT) becomes more attractive to diagnose and propose an assertive treatment plan. This study aimed to evaluate intra and interobserver reproducibility, and concordance of 31 reference points we described considering visualization tools and the three planes of space in a bimaxillary CBCT. Methods. Three observers located in triplicate the 31 reference points in the CBCT of six healthy patients. Friedman test was used to compare intraobserver paired samples, and interobserver concordance was determined by the intraclass correlation coefficient (ICC) with ranges>0.75 (excellent), between 0.60 and 0.74 (good), between 0.40 and 0.59 (sufficient) and<0.40 (poor). The P value was set at<0.05. Results. A high ICC (>0.75%) was obtained by comparing the x, y, and z values at the location of landmark points. Excellent ICC>0.75 was for 81.7% and poor<0.40 was 7.5% in the interobserver evaluation. Data showed that 25 points had excellent concordance on the x-plane, 25 on the y-plane, and 26 on the z-plane (0.75%). Conclusion. Intraobserver concordance analysis indicated that location of anatomical reference points on bimaxillary CBCT is performed with great reproducibility by interpreting their location with a clear description in the three planes of space. Complexity of achieving a good precision degree in the manual marking of reference points caused by convexities of the anatomical structures involved, might explain the variability found. The systematized location of the reference points would contribute to reduce such variability.